INCREASING IN FERTILITY, MELIORATIVE STATE OF SALINE SOILS DUE TO THE ORDER OF PRIORITY. SEEDING OF AGRICULTURAL CROPS - A. Dadakhojhaev; M.A.Xamrakulov; M.Mirsaidov; A.Abdulakimov (Journal of new century innovations, 2023)
Annotation: Salinization and meleoric deterioration of the soil causes great damage to agricultural production. Especially reduces the fertility of the soil and the production of planned agricultural products. At the end of the irrigated arable land, deposits and other lands that are not suitable for agricultural production are formed. This is currently an urgent task which removes harmful salts from the soil, creates and recruits salt-tolerant plants and trees.